BALINESE LIFE IN THE OVERSEAS LAND: An Exploration of the Efforts of Balinese Transmigrants in Maintaining Cultural Identity in Lampung - Hakiki, Kiki Muhamad; Badruzaman; Rohmatika, Ratu Vina; Muttaqien, Zaenal; Hasan Rifai, Epi (Universitas Islam Negeri Raden Intan Lampung, 2025)
The phenomenon of transmigration in Indonesia has brought about various social and cultural changes for relocated communities, including Balinese transmigrants in Lampung. As a group with strong traditions and cultural identity, Balinese transmigrants face challenges in preserving their cultural heritage amidst interactions with diverse local communities. This article aims to explore the efforts made by the Balinese transmigrant community in Lampung to maintain their cultural identity. The study employs a qualitative approach with an ethnographic design, involving in-depth interviews, participatory observation, and document analysis. The findings reveal that Balinese transmigrants have successfully preserved their cultural identity through the continuation of traditional rituals, language, and support from customary institutions and religious organizations. However, the adaptation process also involves adjustments to local culture, creating complex dynamics of acculturation. The implications of this research highlight the importance of social institutions in supporting the continuity of migrant communities’ cultural identity, as well as the relevance of transmigration policies that consider cultural dimensions. These findings contribute to the understanding of how migrant groups can maintain their identity while adapting to new environments, providing insights for further studies on migration and cultural identity in Indonesia.